2020
DOI: 10.1113/ep088812
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in skeletal muscle of fukutin‐deficient mice is resistant to exercise‐ and 5‐aminoimidazole‐4‐carboxamide ribonucleotide‐induced rescue

Abstract: Disruptions in the dystrophin-glycoprotein complex (DGC) are clearly the primary basis underlying various forms of muscular dystrophies and dystroglycanopathies, but the cellular consequences of DGC disruption are still being investigated. Mitochondrial abnormalities are becoming an apparent consequence and contributor to dystrophy disease pathology. Herein, we demonstrate that muscle-specific deletion of the fukutin gene (Myf5/fktn-KO mice (Fktn KO)), a model of secondary dystroglycanopathy, results in ∼30% l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Mutations in the gene for fukutin, FKTN , and subsequent aberrant glycosylation of α-dystroglycan are responsible for dilated CM and several forms of congenital muscular dystrophy, such as LGMD2M. A recent study has shown that muscle-specific deletion of FKTN gene in mice resulted in 16% lower mitochondrial respiratory function and ~30% lower muscle strength compared with healthy littermate controls [ 156 ]. Besides, the expression of the gene for PGC1α, a primary transcription factor for mitochondrial biogenesis, was ~80% lower, which probably contributes to the development of mitochondrial defects.…”
Section: Mitochondrial Dysfunction In Specific Neuromuscular Disordersmentioning
confidence: 99%
“…Mutations in the gene for fukutin, FKTN , and subsequent aberrant glycosylation of α-dystroglycan are responsible for dilated CM and several forms of congenital muscular dystrophy, such as LGMD2M. A recent study has shown that muscle-specific deletion of FKTN gene in mice resulted in 16% lower mitochondrial respiratory function and ~30% lower muscle strength compared with healthy littermate controls [ 156 ]. Besides, the expression of the gene for PGC1α, a primary transcription factor for mitochondrial biogenesis, was ~80% lower, which probably contributes to the development of mitochondrial defects.…”
Section: Mitochondrial Dysfunction In Specific Neuromuscular Disordersmentioning
confidence: 99%
“…The FCMD gene encodes Fukutin, and FCMD is a genetic disease that is caused by an autosomal recessive mutation in the 10-exon of the FCMD gene, leading to muscle weakness, hypotonia, mental retardation, and meningitis in infancy [6,[8][9][10]. A function-deficient mouse model that has been established helped reveal that fukutin is essential for embryonic survival [11] in addition to its vital role in the development of the nervous system [12], heart [13], and skeletal muscle [14,15]. However, the fukutin-deficiency model has only been established in mice.…”
Section: Introductionmentioning
confidence: 99%